FEATURES OF KINETICS OF DECAY AND FORMATION OF STRUCTURE IN СHROMO-MOLYBDENUM-VANADIUM STEEL AT CONTINUOUS COOLING FROM DIFFERENT TEMPERATURES OF AUSTENITIZATION - V. A. Lutsenko; T. N. Golubenko; O. V. Lutsenko; N. A. Glazunova (Литьë и металлургия, 2016)
Influence of austenite grain size of chrome-molybdenum-vanadium steel on formation of structure at continuous cooling has been studied. It is shown, that at the coarsen of grain with increasing temperature of austenitization from 850 till 1050°С stability of the supercooled austenite in structure of chrome-molybdenum-vanadium steel is increased, that is promoted decrease in critical quenching rate.